Are Larger Countries Really More Corrupt? - Knack, Stephen (World Bank, Washington, DC, 2014)
Several authors claim to provide evidence that government corruption is less severe in small than in large countries. The authors demonstrate that this relationship is an artifact of sample selection. Most corruption indicators provide ratings only for the countries in which multi-national investors have the greatest interest. These tend to include almost all large nations but, among small nations, only those that are well governed. The authors find that the relationship between corruption and country size disappears when one uses either a new corruption indicator with substantially increased country coverage or an alternative corruption indicator that covers all World Bank borrowers without regard to country size. They also show that the relationship between corruption and trade intensity--a variable strongly related to population--disappears when samples less subject to selection bias are used.